Inovasi Pengembangan Media Pembelajaran Menurut al-Qur’an - Sakolan Sakolan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This paper aims to describe the use of media from an Islamic perspective. In the world of education, teachers are required to be able to use learning media, which follows the times, and in accordance with the conditions of students. Using a descriptive method, this paper tries to describe the suitability of the theory of learning media with the use of media in the Qur'an and Hadith. In the discussion, it was found that many verses of the Qur'an and the hadith of the prophet are in line with the theory about the use of media today, such as the use of audio, visual media, to multimedia technology-based learning media. It is hoped that after reading this article, the teacher will understand the importance of using media in the view of Islam. Because by using the right media, learning objectives can be achieved well too.